2004
DOI: 10.1088/0268-1242/19/5/004
|View full text |Cite
|
Sign up to set email alerts
|

All-optical wavelength conversion in SOA-based Mach–Zehnder interferometer with monolithically integrated loss-coupled DFB laser diode

Abstract: We demonstrated monolithic integration of a continuous wave probe source consisting of a loss-coupled distributed feedback laser diode (DFB LD) and a Mach-Zehnder interferometric wavelength converter. The integrated device was fabricated using a modified buried ridge stripe (BRS) structure with an undoped InP clad layer on the top of a passive waveguide to reduce high propagation loss. A propagation loss in the passive waveguide as low as 5.29 ± 0.92 dB cm −1 was achieved. For the first time, wavelength conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2005
2005
2006
2006

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The lateral structure of MZI-WC consisted of a modified buried ridge stripe (BRS) structure with an undoped InP clad layer on the top of the passive waveguide to reduce the high propagation loss. The precise fabrication process was described previously [7]. This process has advantages of achieving a low propagation loss in the passive waveguide, good uniformity and moderate current blocking in the active region [7,8].…”
Section: All-optical Mach-zehnder Interferometric Wavelength Converte...mentioning
confidence: 99%
See 2 more Smart Citations
“…The lateral structure of MZI-WC consisted of a modified buried ridge stripe (BRS) structure with an undoped InP clad layer on the top of the passive waveguide to reduce the high propagation loss. The precise fabrication process was described previously [7]. This process has advantages of achieving a low propagation loss in the passive waveguide, good uniformity and moderate current blocking in the active region [7,8].…”
Section: All-optical Mach-zehnder Interferometric Wavelength Converte...mentioning
confidence: 99%
“…Crossphase modulation (XPM) schemes in semiconductor optical amplifiers (SOAs) are a promising candidate for an all-optical wavelength conversion application, because they provide an extinction ratio enhancement for both wavelength down-and up-conversions, high-speed operation, low chirping and high conversion efficiency [2]. Several groups reported SOA-based integrated Michelson (MI) or Mach-Zehnder interferometric (MZI) wavelength converters [3][4][5][6][7][8][9][10][11][12]. However, one problem of the interferometric wavelength converter is a relative small input power dynamic range of about 3-4 dB at 10 Gb s −1 due to its periodic transfer response [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With appropriate dispersion management using either dispersion compensated fiber and/or dispersion shifted fiber this span can normally be extended into regions above 100 km when amplification becomes important [12]. Therefore the majority of the transmission experiments that incorporate EAMs utilise some kind of dispersion management to compensate loss due to large frequency chirp and this is considered to be the weakest point in the use of external EAMs [13]. However, zero chirp or reduced chirp (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…An EAM possesses faster absorption recovery time (i.e., less than 10 ps) and also experiences reduced chirp on the output signal (ideally zero or negative) as compared to other optical devices (e.g., semiconductor optical amplifiers) [20][21][22][23]. Furthermore, it has been suggested that an EAM is (theoretically) capable of handling tera-hertz modulation rates [24].…”
Section: Introductionmentioning
confidence: 99%